RUMAH, LAYAKKAH MENJADI ASET UNTUK INVESTASI? - Chandra Utama (Bina Ekonomi, 2011)
Having own house is part of all families’ dream. Generally house consumes the largest proportion of households’ income. It is not all families can afford to buy them. Furthermore, a house also becomes their most profitable investment.  The rise of price of house, in long period of time, can make household more wealthy than before. Housing investment is worth because several reason. First, it is low risk investment. Second, the return will come from the rent and the rises of price, that believed always increase, could be relatively hight. Third, If is also differ than other portfolio investment, many institutions are willing to give loans to financing the house. As consequency, it gives the owner of houses opportunity to get higher real of return from the investment. House become profitable investment if it done for long period of time. It is also good investment if the price of house always rises. This paper shows the simple rasioning of housing investment. The example is introduced to make clearly explanation.